Larvicidal Activity of The Mixture of Cashew Nut Shell Liquid (CNSL) and Aqueous Extract of Sapindus rarak DC Against Larvae of Culex quinquefasciatus - Fauziah, Rahmi Safarina; Sudarsono, Sudarsono; Mulyaningsih, Budi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
The aim of this study was to evaluate the larvicidal activity of Cashew Nut Shell Liquid (CNSL) against the Culex quinque fasciatus in larval stage. The CNSL was diluted in water by addition of aqueous extract of Sapindus rarak DC to increase its solubility. Larvae were exposed to varying concentrations of that mixture. The larvae mortality was observed after 24 h exposure. LC50 and LC90 value by extrapolation were 20,52 ppm and 55,41 ppm respectively. CNSL were specified by characterizing its physico-chemical properties andÃ‚Â anacardic acid as marker compound by High Performance Chromatography (HPLC). The results were the mixture of Cashew Nut Shell Liquid (CNSL) and Aquous extract of Sapindus rarak DC had larvicidal activity against Cx. Quinque-fasciatus and further investigations were needed to identify the fatty acid derivative as active compound of CNSL whichÃ‚Â responsible for larvicidal activity.